Dynamics of Climate Change and Water Resources of Northwestern Himalaya - Joshi, Rajesh; Kumar, Kireet; Palni, Lok Man S. (Society of Earth Scientists Series, 2015)
This book is about the Himalayan ranges as a source of fresh water supply and a perennial store house of ice, snow and permafrost as well as a vast repository of rich biodiversity, in the light of climate change. Special attention is given to the dynamics of snow and glaciers in the northwestern Himalayas, assessment of climate change patterns, and the consequences of changes and flow regime in order to understand the behaviour of climate change in the northwestern Himalayas. The outcome of melting glaciers are pro-glacial lakes. Their increasing size and potential danger of outbursts requires systematic study, particularly where there is the risk of impact on life and property. Furthermore, the changing trend of the hydrological cycle on a regional or local scale is another area of research which calls for the attention of geoscientists. To date there is a scarcity of reliable data meaning that a concerted effort is still required by all parties.